CYP1A2 is a predictor of HCC recurrence in HCV-related chronic liver disease: A retrospective multicentric validation study. Issue 4 (April 2017) - Sciarra, Amedeo; Pintea, Bogdan; Nahm, Ji Hae; Donadon, Matteo; Morenghi, Emanuela; Maggioni, Marco; Blanc, Jean Frederic; Torzilli, Guido; Yeh, Matthew; Bioulac-Sage, Paulette; Park, Young Nyun; Roncalli, Massimo; et al.
Abstract: Background: Although hepatic resection is a potentially curative treatment for hepatocellular carcinoma (HCC), post-operative prognosis remains unsatisfactory due to the high incidence of recurrence. Several clinicopathological markers have been associated with HCC recurrence, but none has been validated. Extratumoral expression of cytochrome P4501A2 (CYP1A2) was recently proposed as predictor of HCC recurrence. Aims: To validate extratumoral CYP1A2 as predictor of HCC recurrence and to determine its applicability to pretreatment liver biopsy. Methods: Surgically resected HCC (n.180) with clinicopathological data and follow up were retrospectively studied (HCV n.54; HBV n.91; NAFLD/NASH n.35). CYP1A2 expression was evaluated using an immunohistochemical assay and semiquantitative analysis. Results: Etiology-stratified analysis showed that low CYP1A2 expression was independently associated with recurrence-free survival in HCV patients (HR 2.814, 95% CI 1.300–6.093, p = 0.009); this association was lost in the whole cohort. Pretreatment liver biopsy and paired surgical specimens showed concordant CYP1A2 expression in the vast majority of cases (87%), with NPV of 100%, PPV of 81.25%, and a Cohen kappa of 0.72 (substantial agreement). Conclusion: We validated the extratumoral expression of CYP1A2 as a biomarker of HCC recurrence in HCV patients. CYP1A2 analysis in pretreatment liver biopsy can be of help to stratify HCC patients for personalized treatment.